IMPLEMENTATION OF THE INTERNET OF THINGS (IOT) IN REMOTE PATIENT MONITORING SYSTEMS IN HEALTHCARE FACILITIES - Andrayani, Yuan (PT. Hafasy Dwi Nawasena, 2025)
The Internet of Things (IoT) is increasingly adopted in remote patient monitoring systems due to its ability to provide real-time physiological data, enable early detection, and enhance healthcare service quality. This study analyzes IoT implementation in Indonesian healthcare facilities using a Systematic Literature Review approach, selecting 18 high-quality articles from major scientific databases. Literature was reviewed based on methodological rigor and relevance to sensor technologies, data integration, information security, and infrastructure readiness. The findings indicate that IoT significantly improves monitoring effectiveness through automated data acquisition, reduced clinical workload, and enhanced diagnostic accuracy. However, IoT adoption in Indonesia faces challenges including limited network stability, lack of system interoperability, cybersecurity risks, low digital literacy among healthcare workers, and financial constraints. The study concludes that a phased implementation strategy, supported by infrastructure upgrades, staff training, reinforced data protection regulations, and pilot projects is essential for ensuring sustainable IoT deployment in healthcare settings. Such an approach can maximize long-term benefits and support national healthcare transformation.